Determinasi Penggunaan Quick Response Code Indonesian Standard (QRIS) sebagai Alat Pembayaran oleh Pedagang di Taman Kota Singaraja - Ni Luh Sukreni; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study examined the factors influencing the use of the Indonesian Standard Quick Response Code (QRIS) by merchants Taman Kota Singaraja. The implementation of QRIS is part of the payment system digitalization effort to improve transaction efficiency and financial inclusion, but in practice, adoption rates among merchants still vary. This study used a descriptive qualitative approach with a phenomenological method. Data collection techniques were carried out through in-depth interviews, field observations, and documentation involving merchants who are QRIS users, former users, and non-users. Data analysis used NVivo 12 Plus software. The results showed that QRIS use was influenced by perceptions of benefits and ease of use, social influence, and the suitability of QRIS to merchants' operational needs. Conversely, cash transaction habits, technical constraints, and consumers' preference for cash were the main inhibiting factors. The conclusion of this study indicates that the success of QRIS implementation is determined not only by the technological aspect, but also by the merchants' habits and social environment. Therefore, a sustainable and contextual socialization and mentoring strategy is needed to increase QRIS acceptance in the micro-business sector.